Platelets at the Crossroads of Pro-Inflammatory and Resolution Pathways during Inflammation - Nadine Ludwig; Annika Hilger; Alexander Zarbock; Jan Rossaint (Cells, 2022)
Platelets are among the most abundant cells in the mammalian circulation. Classical platelet functions in hemostasis and wound healing have been intensively explored and are generally accepted. During the past decades, the research focus broadened towards their participation in immune-modulatory events, including pro-inflammatory and, more recently, inflammatory resolution processes. Platelets are equipped with a variety of abilities enabling active participation in immunological processes. Toll-like receptors mediate the recognition of pathogens, while the release of granule contents and microvesicles promotes direct pathogen defense and an interaction with leukocytes. Platelets communicate and physically interact with neutrophils, monocytes and a subset of lymphocytes via soluble mediators and surface adhesion receptors. This interaction promotes leukocyte recruitment, migration and extravasation, as well as the initiation of effector functions, such as the release of extracellular traps by neutrophils. Platelet-derived prostaglandin E2, C-type lectin-like receptor 2 and transforming growth factor β modulate inflammatory resolution processes by promoting the synthesis of pro-resolving mediators while reducing pro-inflammatory ones. Furthermore, platelets promote the differentiation of CD4+ T cells in T helper and regulatory T cells, which affects macrophage polarization. These abilities make platelets key players in inflammatory diseases such as pneumonia and the acute respiratory distress syndrome, including the pandemic coronavirus disease 2019. This review focuses on recent findings in platelet-mediated immunity during acute inflammation.